KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN CORPORATE SOCIAL RESPONSIBILITY (CSR), TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Pertambangan Terdaftar Di BEI Periode 2021-2023) - Rocky Romando; Regina Jansen Arsjah (POLITEKNIK LP3I JAKARTA, 2025)
This study examines the impact of institutional ownership, managerial ownership, and corporate social responsibility (CSR) on firm value among mining sector issuers listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Data were sourced from annual reports and sustainability reports and analyzed using multiple linear regression. The results indicate that none of these variables—institutional ownership, managerial ownership, and CSR—have a significant effect on firm value.. These findings suggest that the supervisory roles of institutional and managerial ownership are not yet optimal, and the implementation of CSR has not effectively enhanced firm value strategically. This study recommends better integration of ownership management and CSR with business strategies to improve firm value.